Effect of manganese, zinc, and copper on the biological and osteogenic properties of mesoporous bioactive glass nanoparticles - Westhauser, Fabian; Wilkesmann, Sebastian; Nawaz, Qaisar; Hohenbild, Frederike; Rehder, Felix; Saur, Merve; Fellenberg, Jörg; Moghaddam-Alvandi, Arash; Ali, Muhammad S.; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of biomedical materials research, 2021)
Mesoporous bioactive glass nanoparticles (MBGNs) have demonstrated promising properties for the local delivery of therapeutically active ions with the aim to improve their osteogenic properties. Manganese (Mn), zinc (Zn), and copper (Cu) ions have already shown promising pro-osteogenic properties. Therefore, the concentration-dependent impact of MBGNs (composition in mol%: 70 SiO2, 30 CaO) and MBGNs containing 5 mol% of either Mn, Zn, or Cu (composition in mol%: 70 SiO2, 25 CaO, 5 MnO/ZnO/CuO) on the viability and osteogenic differentiation of human marrow-derived mesenchymal stromal cells (BMSCs) was assessed in this study. Mn-doped MBGNs (5Mn-MBGNs) showed a small “therapeutic window” with a dose-dependent negative impact on cell viability but increasing pro-osteogenic features alongside increasing Mn concentrations. Due to a constant release of Zn, 5Zn-MBGNs showed good cytocompatibility and upregulated the expression of genes encoding for relevant members of the osseous extracellular matrix during the later stages of cultivation. In contrast to all other groups, BMSC viability increased with increasing concentration of Cu-doped MBGNs (5Cu-MBGNs). Furthermore, 5Cu-MBGNs induced an increase in alkaline phosphatase activity. In conclusion, doping with Mn, Zn, or Cu can enhance the biological properties of MBGNs in different ways for their potential use in bone regeneration approaches.
First published: 01 December 2020
Gesehen am 03.12.2021